A SYSTEMATIC LITERATURE REVIEW: SOSIAL MEDIA ORGANIK UNTUK MENDORONG BRAND AWARENESS - Nuran Nuri, Siti; Anshori, Mochammad Isa; Andriani, Nurita (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract: Generic or organic means content that is not paid for by outside stakeholders, created by the brand, but can increase visibility when consumers share it with others. The purpose of this study is to first analyze the potential of organic social media (SMO) to drive brand awareness so that it can further increase sales through social media platforms. Second, what barriers occur in organic social media marketing. By conducting a systematic literature review, this article provides aspects of organic marketing to encourage consumer awareness of a brand. The method used applied Systematic Literature Review (SLR). Based on the systematic literature review, the researcher found 7 final samples out of 304 total articles. The findings show that organic (unpaid) social media can increase visibility when consumers share with others. Organic social media is basically preferred for awareness purposes. Organic social media if used effectively and applying the right strategy, can be a powerful tool for brands to expand the reach of organic posts and increase opportunities for interaction with targets.